2011
DOI: 10.1371/journal.pone.0017576
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Contribution of Epidermal Cell Shape to Petal Wettability Using Isogenic Antirrhinum Lines

Abstract: The petal epidermis acts not only as a barrier to the outside world but also as a point of interaction between the flower and potential pollinators. The presence of conical petal epidermal cells has previously been shown to influence the attractiveness of the flower to pollinating insects. Using Antirrhinum isogenic lines differing only in the presence of a single epidermal structure, conical cells, we were able to investigate how the structure of the epidermis influences petal wettability by measuring the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…2009a). Also, the conical cells of petal epidermises facilitate the physical handling of pollinators (Glover & Martin 1998; Whitney et al . 2009b; 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2009a). Also, the conical cells of petal epidermises facilitate the physical handling of pollinators (Glover & Martin 1998; Whitney et al . 2009b; 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that the microsculpturing of the epidermal cells of petals influences the optical and adhesive properties of plant tissues (Wagner et al 2003;Pfündel et al 2006;Whitney et al 2011). High-resolution imaging of both the adaxial and the abaxial petal epidermises of O. pes-caprae revealed a relief at the nanometer scale (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Conical cells have several biological functions related to pollinator attraction, including scent production (Kolosova et al. , 2001; Whitney et al. , 2009a,b, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…), reducing petal wettability (Whitney et al . ) and altering overall petal shape by changing the direction of cell expansion in the epidermis (Baumann et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Field trials of Antirrhinum majus showed that when pollinator number limits seed set, plants with conical petal cells set more seed than flat-celled plants (Glover & Martin 1998). There may be many reasons for this, as conical petal cells have diverse effects on a flower, including enhancing colour, slightly increasing floral temperature (Comba et al 2000;Whitney et al 2011a), reducing petal wettability (Whitney et al 2011b) and altering overall petal shape by changing the direction of cell expansion in the epidermis (Baumann et al 2007). Bees are able to use most of these traits as learned indicators of rewards, and some (such as temperature) are traits that a bee will seek out as a reward in itself (Dyer et al 2006;Rands & Whitney 2008).…”
Section: Introductionmentioning
confidence: 99%